Recent Advances in Polymers as Matrices for Drug Delivery Applications - Zoilo González; Ana Ferrandez-Montero; Juan Domínguez-Robles (MDPI AG, 2023)
Polymeric-based drug delivery systems have become versatile and valuable candidates in sectors such as pharmaceuticals, health, medicine, etc [...]